Resolution of experimental and tick-borne Borrelia burgdorferi infection in mice by passive, but not active immunization using recombinant OspC - Zhong, Weimin; Gern, Lisa; Stehle, Thomas; Museteanu, Crisan; Kramer, Michael D.; Wallich, Reinhard; Simon, Markus M. (European journal of immunology, 1999)
Vaccination with outer surface protein A (OspA) of Borrelia burgdorferi prevents subsequent infection and disease in both laboratory animals and humans with high efficacy. OspA-based immunity, however, does not affect established infection due to the loss of OspA expression in the vertebrate host. We show here that repeated passive transfer of mouse and/or rabbit immune sera to recombinant GST-OspC fusion protein resulted in a dose-dependent resolution (1) of fully established arthritis and carditis as well as infection in needle-challenged C.B-17 SCID and (2) of infection in both experimentally and tick-infected BALB/c mice. Unexpectedly, active immunization of disease-susceptible AKR/N mice with GST-OspC only led to prevention but not resolution of disease and infection, in spite of high serum titers of OspC-specific Ab and the expression of ospC in tissue-derived spirochetes. The data suggest that the efficacy of OspC antibody-mediated immunity depends on the immunological history of the recipient and/or environment-dependent regulation of OspC surface expression by spirochetes in vivo. The results encourage further attempts to develop therapeutic vaccination protocols against Lyme disease.